#TITLE_ALTERNATIVE# - KUSUMANINGRUM (NIM : 12209074), FATIMAH
In determining well production rate, we need to consider the capacity of surface facilities such as separators that limit field production rate. Thus, it is necessary to allocate production rate for each well. Allocation factor is the ratio of individual well production rate to the total field production rate. There is no practical method that can be used to allocate production rate in the field. Therefore, a new allocation factor equation that is easy to use, proportional to well deliverability, and able to avoid the occurrence of backpressure is developed. This equation is established based on statistical data of integrated simulation results using Petrel™, Pipesim™, and FPT™. Then multiple linear regression is performed to establish this equation model.